Hydrogel‐based composites: Unlimited platforms for biosensors and diagnostics. Issue 6 (4th May 2021) - Wang, Zeyi; Liu, Yanlei; Wang, Zhiwei; Huang, Xiao; Huang, Wei
Abstract: The need for biosensing systems, which are capable of reliable and accurate detection of physiological signals and disease biomarkers along with biocompatible surface chemistry and textures for device–human interface, has driven the continuous search for advanced sensing materials, sensing strategies, and device structures. Hydrogels are hydrophilic polymers with high water content and thus akin to human tissues. They are not only able to act as polymeric matrices to load functional materials for bio‐signal transducing, but also stimuli‐responsive to cooperate with the filler materials for further enhanced sensing performance. A vast combination of hydrogels and functional fillers such as biomacromolecules, metal nanostructures, carbon nanomaterials, and two‐dimensional materials beyond graphene has been demonstrated over the last decade for fabrication of biosensors for disease diagnosis and health monitoring. This review article aims to provide an overview of the various hydrogel‐based composites, introduce their preparation protocols, and describe the working principles of their corresponding sensors. Recent development of these sensors for potential diagnosis of diseases such as diabetes, cancers, and cardiovascular diseases is then summarized, followed by stating the current challenges and prospects in this field.